CONTENT AND STRUCTURE OF SELF-EDUCATIONAL COMPETENCE OF FUTURE BACHELORS IN ECONOMICS: CATEGORICAL AND DEFINITIONAL ANALYSIS - Piven Yaroslav (Alfred Nobel University Publisher, 2023)
The article carries out a categorical and definitional analysis of the self-educational competence phenomenon of future bachelors in economics, analyses the concepts of «self-education», «self-educational activity», «competence», «self-educational competence». It has been emphasized that, along with indicators of professional mastery, future specialists, for the sake of their self-efficacy and professional success, are called to become proficient in the knowledge, skills and experience of self-education, as well as to develop professionally important personal qualities - cognitive independence, cognitive activity, the ability for professional self-development and self-improvement via specially organized self-study. The purpose of the article is to determine the essence and structure of self-educational activity and self-educational competence and their specific content for future bachelors of economics. To implement the set tasks, in the study, a number of methods are used; among them a categorical and definitional analysis of scientific research enlightened the essence of self-education and self-educational competence, modelling of components of self-educational competence, specification and systematization of existing theoretical works to determine the structure of self-educational competence of future bachelors in economics. Self-education in the context of future bachelors of economics professional training is defined as a type of basic and professional education directed at systematic, purposeful, continuous improvement of knowledge, abilities and skills necessary for successful performance of one's activities and achievement of certain personal and social significant goals. It has been established that the goal of students' self-education is the achievement of certain personally significant educational aims, the satisfaction of cognitive interests, general cultural and professional requests, and qualitative changes of personality in the process of independent acquisition of subjectively and objectively new knowledge. It has been found that the crucial characteristics of self-education are self-governance, self-organization, self-efficacy, self-activity, internal freedom, voluntariness, self-regulation, focus on self-improvement and self-realization. It has been substantiated that self-educational competence is a crucial component of the future specialists' professional competence, a person's integrative property, which allows them to achieve productivity and success in self-educational activities, receive a quality education, master the profession, and achieve necessary qualifications. The self-educational competence of future bachelors in economics is presented from the point of view of the structure of self-educational activity, which covers the motivational and value aspect (needs, motives, instructions and attitude); knowledge-based aspect (special knowledge); the activity-based aspect (ability, skills, competences), the reflective aspect (that which characterizes the products of self-educational activity in external and internal plans) and the personal aspect (specific features and qualities that enable self-educational activity). Self-educational competence is revealed as a multidimensional personal formation that encompasses a number of other competencies including moral and ethical, general educational, subject, methodological, informational, digital, general cultural ones, and competence in self-development. It has been concluded that the formation of self-educational competence should be a mandatory component of the content of studies in higher education institutions and the system of professional training of future bachelors in economics.